Increased intracranial arterial tortuosity is associated with worse cardiovascular outcome in patients with Loeys-Dietz syndrome. (February 2022) - Vornetti, Gianfranco; Spinardi, Luca; Mariucci, Elisabetta; Graziano, Claudio; Baroni, Maria Chiara; Faccioli, Luca; Donti, Andrea
Highlights: Patients with higher tortuosity showed a greater incidence of aortic surgery. A longer surgery-free survival was associated with lower tortuosity. Arterial tortuosity can be easily quantified on brain MRA. Abstract: The aim of our study was to evaluate the association between intracranial arterial tortuosity and cardiovascular outcome in patients with Loeys-Dietz syndrome (LDS). We performed a retrospective analysis of all patients with genetically confirmed LDS who underwent at least one brain MRA at our institution (n = 32); demographic and clinical features were evaluated in relation to the tortuosity of intracranial arteries as measured by tortuosity index (TI), which was calculated using the formula: [(centerline length) / (straight-line length)-1] × 100. Receiver operating characteristic curve analysis for intracranial TI and the binary end point of aortic surgery showed vertebrobasilar TI (VBTI) to be the best classifier among the examined arterial segments (AUC = 0.822). Patients with higher VBTI showed a greater incidence of aortic surgery (p < 0.001) and underwent more surgical and endovascular procedures (p = 0.006), with a higher rate of operations (p = 0.002). Kaplan-Meier analysis showed a significantly longer surgery-free survival in patients with lower arterial tortuosity (p < 0.001). At multivariate analysis, higher VBTI was associated with an increased risk of surgery (p < 0.001), which was independent of gene mutation and patient age. Increased VBTI is a marker of adverse cardiovascular outcome in patients with LDS, which can be easily measured on brain MRA, and may be useful in the management of this heterogeneous patient population.